MODEL OF STUDENT INVESTMENT INTENTION WITH FINANCIAL KNOWLEDGE AS A PREDICTOR THAT MODERATED BY FINANCIAL SELFEFFICACY AND PERCEIVED RISK - Elfahmi, Ryan; Ikin Solikin; Nugraha (Dinasti Publisher, 2020)
This study aims to predict students' investment intentions in the Indonesia Stock Exchange. The questions in this study are whether financial knowledge shows a significant effect on student investment intentions on the Indonesia Stock Exchange, whether financial self-eficacy shows a significant effect in strengthening or weakening student investment intentions on the Indonesia Stock Exchange and whether the perceived risk shows a significant effect in strengthening or weakening student investment intentions in the Indonesia Stock Exchange. The analysis technique in this study using SPSS ver.21 and analyzed by regression PROCESS v3.4 by Andrew F. Hayes. The sampling method is purposive sampling, with several criteria developed previously. Questionnaires are used to collect data from respondents. Respondents in this study were students at the University of Pamulang, South Tangerang. A total of 400 respondents participated. Based on the analysis, Financial Knowledge influences students' investment intentions on the Indonesia Stock Exchange. Financial self-efficacy does not shows a significant influence in strengthening student investment intentions on the Indonesia Stock Exchange. The perceived risk shows a significant effect in weakening students' investment intentions on the Indonesia Stock Exchange.